ANALISIS AKUNTABILITAS, TRANSPARANSI DAN KUALITAS PELAYANAN TERHADAP MINAT MUZAKKI MEMBAYAR ZAKAT DI YAYASAN DANA SOSIAL AL-FALAH MALANG - Sya'bandani, Fadhil Yuda; M. Pudjihardjo (Fakultas Ekonomi dan Bisnis Universitas Brawijaya, 2023)
Zakat is an alternative solution provided by Islam for the welfare of the people. In 2022, ZIS funds collected will reach 22 trillion, this number has increased by 84.16 percent compared to 2021. However, in reality zakat management institutions in Indonesia are still not at the best level in terms of collection. According to a survey, people are more likely to pay through mosques (37%), through BAZNAS (25%), directly to Mustahik (23%) and through LAZ (15%). This research aims to examine the influence of accountability, transparency and service quality on muzakki's interest in paying zakat at the Al-Falah Social Fund Foundation, Malang City. The type of research used is quantitative using a questionnaire. The population in this research was muzakki from the Al-Falah Social Fund Foundation, Malang City in 2022. Meanwhile, the sample used was 100 respondents. The sampling method used was random sampling. The data used in the research is primary data. The data collection technique for this research uses a questionnaire. The results of this research show that the variables of accountability, transparency and service quality have a significant positive effect on muzakki's interest in paying zakat at the Al-Falah Social Fund Foundation, Malang City. It is hoped that this research will be a consideration for the community in choosing the Malang City Al-Falah Social Fund Foundation as a place to distribute their zakat.